Implementation Of Geolocation Method Using Haversine Model on Internship Presence System: Case Study in One of The State-Owned Enterprises - Jaelani, Jaelani; Rosadi, Dadi; Hermanto, Cahyo; Oktavia, Oktavia (Electronic, Business, Management and Technology Journal, 2024)
Attendance is a critical metric in assessing internship participants, impacting their total evaluation during the internship duration. A state-owned firm presently employs a manual attendance system utilizing a logbook, susceptible to recording inaccuracies and data tampering. This study seeks to develop a web-based attendance system that employs geolocation techniques, enabling interns to check in without completing a logbook. This system uses the Haversine model to compute a maximum distance of 500 meters from a specified work site to guarantee the precision of attendance data. This research also examines absence resulting from illness or authorized leave. Rapid Application Development (RAD), utilizing Unified Modeling Language (UML) for system design, is the methodology employed in creating this attendance system. The system is coded utilizing the PHP programming language and the MySQL database. This research culminates in developing a web-based attendance system that allows interns to check in at their work sites efficiently and correctly, thereby diminishing reliance on the manual logbook system. This research entails improved precision in attendance documentation, heightened efficiency in overseeing intern assessments, and augmented accountability among interns. By applying this method, the state-owned firm can more effectively evaluate intern performance and make informed decisions concerning its organizational development and contributions.